Digest of U-Report surveys: 4th quarter of 2022 (media literacy, youth councils, benefits from volunteering) - Demchuk V. S. (Український соціум, 2022)
The results of surveys of the innovative youth project U-Report for October – December 2022 on media literacy, youth councils, benefits from volunteering.